2011
DOI: 10.1088/1748-0221/6/01/c01031
|View full text |Cite
|
Sign up to set email alerts
|

Study of charge-sharing in MEDIPIX3 using a micro-focused synchrotron beam

Abstract: X-ray photon-counting detectors consisting of a silicon pixel array sensor bumpbonded to a CMOS electronic readout chip offer several advantages over traditional X-ray detection technologies used for synchrotron applications. They offer high frame rate, dynamic range, count rate capability and signal-to-noise ratio. A survey of the requirements for future synchrotron detectors carried out at the Diamond Light Source synchrotron highlighted the needs for detectors with a pixel size of the order of 50µm. Reducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 16 publications
(21 reference statements)
1
40
0
Order By: Relevance
“…Currently the telescope resolution of 2.3µm gives a more exact position of the particle's point of incidence than the 4.5µm FWHM of the micro-focused beam achieved in the first study here. Since completion of this experiment it has been demonstrated that the beam size can be reduced to a FWHM of 2.2µm and the background present greatly reduced by detuning the monochromator in order to suppress higher harmonics present in the beam [20].…”
Section: Discussionmentioning
confidence: 99%
“…Currently the telescope resolution of 2.3µm gives a more exact position of the particle's point of incidence than the 4.5µm FWHM of the micro-focused beam achieved in the first study here. Since completion of this experiment it has been demonstrated that the beam size can be reduced to a FWHM of 2.2µm and the background present greatly reduced by detuning the monochromator in order to suppress higher harmonics present in the beam [20].…”
Section: Discussionmentioning
confidence: 99%
“…Energy ranges are user-defined, therefore offering flexibility and customization for a wide range of medical and industrial applications. To reduce the effect of charge sharing [42], the charge summing feature is included in the Medipix3RX ASIC which allows the total charge for a single interaction to be summed and allocated to the closest pixel [43]. To do this, each pixel communicates with its four neighbours to locate the pixel with the highest charge for a co-incident event, the total charge is then allocated to this pixel [42].…”
Section: Mars Spectral Scannermentioning
confidence: 99%
“…To reduce the effect of charge sharing [42], the charge summing feature is included in the Medipix3RX ASIC which allows the total charge for a single interaction to be summed and allocated to the closest pixel [43]. To do this, each pixel communicates with its four neighbours to locate the pixel with the highest charge for a co-incident event, the total charge is then allocated to this pixel [42]. The threshold settings for the selection of energy bins have a major impact on spectral image quality in terms of image contrast and noise level.…”
Section: Mars Spectral Scannermentioning
confidence: 99%
“…It is activated in order to eliminate the effect due to charge being shared between adjacent pixels as a consequence of charge diffusion in the sensor material [19], which is more significant the smaller the pixel pitch and the thicker the sensor. In CSM, a pixel communicates with its neighbours in order to (1) reconstruct the charge from a single photon interaction that is spread in a cluster of pixels and (2) assign the reconstructed charge to a single pixel (the pixel with the largest charge deposition).…”
Section: A Medipix3rx Asicmentioning
confidence: 99%
“…This is defined as charge sharing effect and is stronger for sensors with small pixel area to sensor thickness ratio. The resulting charge sharing effect is discussed in [19], [27]. In order to reduce the count loss due to the charge sharing effect, the threshold discriminator is set at half of the impinging X-ray energy.…”
Section: Charge Collectionmentioning
confidence: 99%